Accentedness Ratings of English Loanwords by Acadian French Listeners - Harriott, Phillip; Cichocki, Wladyslaw (Revue québécoise de linguistique)

(untitled) (Université du Québec à Montréal, 1993)
AbstractThis study investigates how native speakers of Acadian French evaluate the accentedness of loanwords entering their language from English. 83 university students, who were divided into three levels of proficiency in English, rated eight loanwords. The loans were chosen to represent a range of phonetic and social integration. Results show that listeners' proficiency in English is a significant factor in the rating: listeners with high English proficiency are more lenient with English pronunciations of a loanword than are low English proficient listeners. While significant individual differences were found in the ratings of the target loanwords, the relation between the accentedness rating of a loanword and its degree of social integration appears to be unclear.